2016
DOI: 10.4093/dmj.2016.40.4.326
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Novel Glucose Area Under the Curve (AUC) Monitoring System: Comparison with the AUC by Continuous Glucose Monitoring

Abstract: BackgroundManagement of postprandial hyperglycemia is a key aspect in diabetes treatment. We developed a novel system to measure glucose area under the curve (AUC) using minimally invasive interstitial fluid extraction technology (MIET) for simple monitoring of postprandial glucose excursions. In this study, we evaluated the relationship between our system and continuous glucose monitoring (CGM) by comparing glucose AUC obtained using MIET with that obtained using CGM for a long duration.MethodsTwenty diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…The mean percentage error of the regression analysis was 19.7%. These data are consistent with those previously performed for 2 hours during OGTT or after a meal [ 13 18 19 ].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The mean percentage error of the regression analysis was 19.7%. These data are consistent with those previously performed for 2 hours during OGTT or after a meal [ 13 18 19 ].…”
Section: Resultssupporting
confidence: 92%
“…However, frequent CGM can be burdensome for patients. We have previously evaluated IG AUC for 2 to 4 hours using this system [ 11 13 18 19 ] and found that this system was useful in detecting plasma glucose excursion and peak plasma glucose levels after 75-g OGTT [ 12 18 ]. We first applied this system to measure IG AUC for 8 hours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The area under the curve (AUC) of glucose levels > 180 mg/dL (AUC 180 ) and < 70 mg/dL (AUC 70 ) was represented as hyperglycemic and hypoglycemic periods, respectively. AUC t and AUC n represent the total and normal (70–180 mg/dL) AUCs for glucose levels, respectively [ 18 ]. The low blood glucose index (LBGI) and high blood glucose index (HBGI) were calculated based on glucose levels and represented the risk of hypoglycemia and hyperglycemia, respectively [ 19 ].…”
Section: Methodsmentioning
confidence: 99%